PENINGKATAN KUALITAS TATA KELOLA SAMPAH MELALUI PEMBERDAYAAN MASYARAKAT DI DESA SANUR KAUH, KECAMATAN DENPASAR SELATAN, KOTA DENPASAR: Improving The Quality Of Waste Governance Through Community Empowerment In Sanur Kauh Village, South Denpasar District, Denpasar City - Tantra, I Gusti Lanang Putu; Aryawan, I Gede; Murthi, Ngurah Wisnu (Yayasan Al-Amin Qalbu, 2024)
The main aim of improving the quality of waste management through community empowerment in Sanur Village with 3R waste sorting is to achieve a cleaner, healthier and more sustainable environment. The method of implementing the service includes: 1) Preparation stage, 2) First implementation stage, coordination with waste managers, 3) Second implementation stage, everything that has been planned and discussed with waste managers is applied to residents, 4) Third implementation stage is looking for solutions to priority waste problems in Sanur village kauh, and 4) Evaluation stage. The results of the service show that improving the quality of waste management through community empowerment in Sanur Village with 3R waste sorting is a very important step in creating a clean, healthy and sustainable environment. By involving all levels of society, this program can provide enormous benefits for the people of Sanur Village and the surrounding environment. The 3R waste sorting program in Sanur Village has shown very encouraging results. By involving all stakeholders and implementing a comprehensive approach, this village has succeeded in reducing the amount of waste disposed of in the landfill, improving environmental quality